New Artificial Urinary Sphincter Devices in the Treatment of Male Iatrogenic Incontinence - Ioannis Vakalopoulos; Spyridon Kampantais; Leonidas Laskaridis; Vasileios Chachopoulos; Michail Koptsis; Chrysovalantis Toutziaris (Advances in Urology)
Severe persistent stress incontinence following radical prostatectomy for prostate cancer treatment, although not very common, remains the most annoying complication affecting patient’s quality of life, despite good surgical oncological results. When severe incontinence persists after the first postoperative year and conservative treatment has been failed, surgical treatment has to be considered. In these cases it is generally accepted that artificial urinary sphincter is the gold standard treatment. AUS 800 by American Medical Systems has been successfully used for more than 35 years. Recently three more sphincter devices, the Flow-Secure, the Periurethral Constrictor, and the ZSI 375, have been developed and presented in the market. A novel type of artificial urinary sphincter, the Tape Mechanical Occlusive Device, has been inserted in live canines as well as in human cadavers. These new sphincter devices are discussed in this paper focusing on safety and clinical results.